PENGARUH INFORMASI KERJA DAN PENGALAMAN PRAKTIK INDUSTRI PADA KESIAPAN KERJA SISWA SMK - Zamtinah Zamtinah (Universitas Negeri Yogyakarta, 2003)
Abstract This research aims to find out the influence of employment-world information and industry practice experience toward the readiness of work-mental of the students in vocational school. The population of this research is all the third grade students of electrical engineering, SMK N 3 Yogyakarta. The data obtained was analyzed by using the technique of two predictors’ double regression with significant rate of 5%. The analysis result shows that: (1) the level of work mental readiness of the third grade students of Electrical Engineering, SMKN 3 Yogyakarta is very high with mean value 82.32; (2) There is influence of employment-world towards the readiness of work-mental at the significance rate of 5% with the regression coefficient of (b) = 0.418 and the amount of the effective information contribution of employment-world is 16.956%; (3) Ther is influence of industrial practice experience towards the readiness of work-mental at the significance rate of 5% with regression coefficient (b)= 0.641 and the amount of the effective information contribution of work-world is 25.725%; (4) There is a united influence between employment-world information and industrial practice experience toward the readiness of work-mental at the significance rate of 5% with the determination coefficient of 0.427. analysis result of two predictors regression found F=39.842. Keywords: employment-world information, industry practice experience, work-mental readiness.